Violacein as a genetically-controlled, enzymatically amplified and photobleaching-resistant chromophore for optoacoustic bacterial imaging - Jiang, Yuanyuan; Sigmund, Felix; Reber, Josefine; Dean-Ben, Xose Luis; Glasl, Sarah; Kneipp, Moritz; Estrada, Hector; Razansky, Daniel; Ntziachristos, Vasilis; Westmeyer, Gil G. (Scientific Reports, 2015)
There is growing interest in genetically expressed reporters for in vivo studies of bacterial colonization in the context of infectious disease research, studies of the bacterial microbiome or cancer imaging and treatment. To empower non-invasive high-resolution bacterial tracking with deep tissue penetration, we herein use the genetically controlled biosynthesis of the deep-purple pigment Violacein as a photobleaching-resistant chromophore label for in vivo optoacoustic (photoacoustic) imaging in the near-infrared range. We demonstrate that Violacein-producing bacteria can be imaged with high contrast-to-noise in strongly vascularized xenografted murine tumors and further observe that Violacein shows anti-tumoral activity. Our experiments thus identify Violacein as a robust bacterial label for non-invasive optoacoustic imaging with high potential for basic research and future theranostic applications in bacterial tumor targeting.
CRIS-Team Scopus Importer:2023-03-08